Propuesta de un manual educativo basado en saberes ancestrales y oralidad con portadores de saberes para el fortalecimiento de la enseñanza de Ciencias Sociales en la Educación Intercultural Bilingüe de la comunidad Gradas, cantón Guaranda, provincia de Bolívar, año 2025. - Garzón Bastidas, Gladys Yajaira (2025)
This research aims to strengthen the teaching of Social Studies within Intercultural Bilingual Education through the development of an educational manual based on ancestral knowledge and the oral traditions of knowledge bearers from the Gradas community, Guaranda canton, Bolívar province. The methodology applied was qualitative with an ethnographic approach, allowing for an understanding of the community’s cultural practices, traditions, and ways of transmitting knowledge. Through interviews, observations, and participatory workshops, valuable contributions were collected and integrated into the proposed educational manual. This material seeks to revalue local knowledge, promote intercultural respect, and reinforce students’ cultural identity. As a result, a pedagogical resource is proposed that integrates ancestral wisdom with the curricular content of Social Studies, contributing to meaningful learning and the preservation of cultural memory.